SISTEM MONITORING REALTIME DETAK JANTUNG DAN KADAR OKSIGEN DALAM DARAH PADA MANUSIA BERBASIS IoT (INTERNET of THINGS) - Aprilia Aprilia; Tan Suryani Sollu (Foristek, 2020)
Heart rate and oxygen levels in the blood are very important for medical personnel to know the patient's health condition, with the existing real-time of heart rate monitoring system and oxygen levels in the blood based on IoT, it can facilitate the workload of medical personnel. This tool uses the Max30100 sensor to detect heart rate and oxygen levels in the blood and NodeMCU ESP8266 as controlling and sending sensor data to the IoT platform on android and PC wirelessly. The results of sending heart rate data and oxygen levels in the blood on Blynk and web servers have an error alignment average of 1.7% and 0%. and measurements have an average of 87 bpm and 96% of SpO2 in adolescents 20-24 years with the results of the measurements indicate the patient's condition is normal.